Relativization strategies and sociolinguistic variation in spoken Italian: a typological account - Silvia Ballarè (Linguistic Typology at the Crossroads)
In this paper I aim at describing and analysing relative clauses in a corpus of spoken Italian. In the first section, I provide an overview of the relativization strategies in Italian, also taking into account non-standard varieties; then, I briefly discuss the sociolinguistic characterization of the sub-standard area of contemporary Italian. In § 2, I introduce the selected corpus and its characteristics, also explaining the methodologies adopted for data extraction and annotation. Then, in § 3, the results of the analysis are presented. The distributions of the different strategies and the outputs of a statistical analysis show the different importance assumed by both linguistic and extralinguistic factors and enable the explanation of the observed variability. Finally, in § 4, some general conclusions are drawn.